Multinational Trends and Applications Considering Oncologic Risk Potential in Autologous Fat Grafting in the Face and Neck - Fiedler, Lukas; Saleh, Daniel B.; Mukrowsky , Alicia (New Horizons in Medicine and Medical Research Vol. 11, 2022)
Autologous fat grafting (AFG) is gaining popularity in both aesthetic and reconstructive procedures, since the body of evidence for its use has expanded. We sought to review contemporary harvesting and processing techniques for AFG in the craniofacial region. We conducted a survey in four European nations to assess the clinical impact of oncological risk. We identified no major geographical differences in harvesting and processing techniques between the German-speaking and English-speaking groups. The probability of AFG's pro-oncologic conduct is discussed by half of our respondents. AFG harvesting and processing techniques don’t considerably vary by geography. Further research into the oncologic risk potential of AFG in head and neck tumor sites is needed, especially because there is no outstanding paper on the subject.